2019
DOI: 10.1002/anie.201813771
|View full text |Cite
|
Sign up to set email alerts
|

Nanozyme‐Catalyzed Cascade Reactions for Mitochondria‐Mimicking Oxidative Phosphorylation

Abstract: Multiple-enzyme-involving cascade reactions that yield bioenergy are necessary in natural oxidative phosphorylation. However,i nv itro applications are hampered by the sensitivity of catalytic activity to environmental adaptation. Herein, we explore nanozyme-catalyzed cascade reactions in an assembled hybrid architecture for mitochondria-mimicking oxidative phosphorylation. Hollows ilica microspheres containing trapped gold nanoparticles were synthesized to promote two enzyme-like catalytic reactions that tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 66 publications
1
81
0
Order By: Relevance
“…Furthermore, R‐CMs possessed strong near‐infrared (NIR) absorbance and outstanding photothermal effects with a rapid elevating temperature under 808 nm light irradiation (Figure b), which was beneficial in enhancing the elimination of bacteria. Meanwhile, the photothermal effect could also slightly enhance the peroxidase‐like activity (Supporting Information, Figure S29), which has been reported by previous studies . Encouraged by the integrated bacteria‐capture behavior and intrinsic enhanced peroxidase‐like activity as well as photothermal performance, we assessed the antibacterial potential of R‐CMs by a growth‐inhibition assay in liquid medium and the spread plate method (Figure c–e).…”
Section: Resultssupporting
confidence: 62%
“…Furthermore, R‐CMs possessed strong near‐infrared (NIR) absorbance and outstanding photothermal effects with a rapid elevating temperature under 808 nm light irradiation (Figure b), which was beneficial in enhancing the elimination of bacteria. Meanwhile, the photothermal effect could also slightly enhance the peroxidase‐like activity (Supporting Information, Figure S29), which has been reported by previous studies . Encouraged by the integrated bacteria‐capture behavior and intrinsic enhanced peroxidase‐like activity as well as photothermal performance, we assessed the antibacterial potential of R‐CMs by a growth‐inhibition assay in liquid medium and the spread plate method (Figure c–e).…”
Section: Resultssupporting
confidence: 62%
“…Meanwhile,t he photothermal effect could also slightly enhance the peroxidase-like activity (Supporting Information, Figure S29), which has been reported by previous studies. [18,48] Encouraged by the integrated bacteriacapture behavior and intrinsic enhanced peroxidase-like activity as well as photothermal performance,w ea ssessed the antibacterial potential of R-CMs by ag rowth-inhibition assay in liquid medium and the spread plate method (Figure 4c-e). Thec hanges in bacterial morphology induced by the antibacterial system were observed by SEM (Figure 4f).…”
Section: Methodsmentioning
confidence: 99%
“…[2,3] Recently,the burgeoning nanozymes have emerged as anew generation of antibiotics due to their broad-spectrum antimicrobial activity,n egligible toxicity,a nd the lack of resistance towards nanozymes. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Typically,ananozyme that acts as ap eroxidase mimic specifically catalyzes the con-version of H 2 O 2 into highly toxic reactive oxygen species (ROS), such as hydroxyl radical (COH), to attack the bacterial membrane at mildly acidic infectious sites.H owever,t he insufficient bacteria-capturing capacity of nanostructures as well as the relatively low ability to generate ROS,i nherent short lifespan, and limited diffusion distance of ROSseverely restrict the therapeutic activity of almost all nanozymes. [19,20] To overcome this issue,integration of multiple components or surface-modification strategies have been applied to improve the antibacterial effects, [4,9,10,13,14] but this comes out at the cost of either wasting antimicrobial material or blocking active sites,a nd could even cause toxicity.T herefore,i ti s urgently needed to find an ew way to engineer nanozymes with both inherent bacteria-binding ability and enhanced catalytic activity to improve their therapeutic outcomes without potential safety hazards.…”
Section: Introductionmentioning
confidence: 99%
“…There are many strategies for constructing multienzyme catalysis, such as co-immobilization of enzymes, conjugation of natural enzymes with artificial enzymes (i.e. nanozymes), and enhancing the function of enzymes within cell-free metabolic pathways [59,65,77,[93][94][95][96][97]. Encapsulation is a common form to maintain a high local concentration of enzymes and protect them from biological damage through proteases.…”
Section: Multi-enzyme Systemmentioning
confidence: 99%
“…The challenge is, however, that not all enzymes will manifest activity enhancement when binding to the same quantum dots. Li et al reported a bio-inspired nanozyme-based multienzyme system which consisted of Au nanoparticles with two enzyme-like activities and ATP synthase, by mimicking mitochondrial oxidative phosphorylation [97]. In this system, the intrinsic glucose oxidase and peroxidase activities of Au nanoparticles provided favorable proton gradient, driving the oxidative phosphorylation of ATP synthase as efficiently as natural mitochondria.…”
Section: Multi-enzyme Systemmentioning
confidence: 99%